Peranan Tungau Debu Rumah Pada lgE Dermatitis Atopik - Betty Ekawati Suryaningsih; Punik Mumpuni Wijayanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2009)
Atopic dermatitis is hypersensitivity respond that occurs by exposure to allergens environment, which is inheritance in familial pattern. The role of lgE is importance in pathogenesis of atopic dermatitis. Exposure of House dust mite could be JgE specific laboratory examinations were increased and causing relapse of Atopic dermatitis, the patch tests used of house dust mite result are positive in atopic dermatitis.